OPTIMISING INTERNSHIP PROGRAMMES: BUILDING SKILLS AND COMPETENCIES OF PUBLIC ADMINISTRATION STUDENTS AT PUANGRIMANGGALATUNG UNIVERSITY - Irwan, Irwan; Asmanurhidayani, Asmanurhidayani; Erna, Erna (Transpublika Publisher, 2024)
This research explores the effectiveness of the internship program in preparing students for professional careers in the Public Administration Department of Puangrimanggalatung University. It examines both the implementation of the program and the factors influencing its success and challenges. Utilizing a qualitative approach, the study involved interviews with internship students, recipient agencies, and the Dean of the Faculty of Social Sciences. Data was analyzed through content analysis to identify key themes and patterns. The findings reveal discrepancies between the program's execution and the regulations set by the Ministry of Education and Culture of the Republic of Indonesia, notably the shorter internship duration of one month versus the mandated 3-6 months. Additionally, while students benefit from the flexibility to select their internship sites based on their interests, a major challenge is the insufficient communication between the faculty, students, and recipient agencies. The study concludes that improving adherence to regulations and enhancing communication could significantly benefit the internship program's effectiveness.